Membrane-induced organization and dynamics of the N-terminal domain of chemokine receptor CXCR1: insights from atomistic simulations - Kharche, Shalmali; Joshi, Manali; Sengupta, Durba; Chattopadhyay, Amitabha (Chemistry and Physics of Lipids, 2018)
The CXC chemokine receptor 1 (CXCR1) is an important member of the G protein-coupled receptor (GPCR) family in which the extracellular N-terminal domain has been implicated in ligand binding and selectivity. The structure of this domain has not yet been elucidated due to its inherent dynamics, but experimental evidence points toward membrane-dependent organization and dynamics. To gain molecular insight into the interaction of the N-terminal domain with the membrane bilayer, we performed a series of microsecond time scale atomistic simulations of the N-terminal domain of CXCR1 in the presence and absence of POPC bilayers. Our results show that the peptide displays a high propensity to adopt a beta-sheet conformation in the presence of the membrane bilayer. The interaction of the peptide with the membrane bilayer was found to be transient in our simulations. Interestingly, a scrambled peptide, containing the same residues in a randomly varying sequence, did not exhibit membrane-modulated structural dynamics. These results suggest that sequence-dependent electrostatics, modulated by the membrane, could play an important role in folding of the N-terminal domain. We believe that our results reinforce the emerging paradigm that cellular membranes could be important modulators of function of G protein-coupled receptors such as CXCR1.
Keywords: All atom MD simulations; beta-sheet; CXCR1; Membrane interaction; N-terminal

Superior HIV-1 TAR binders with conformationally constrained R52 arginine mimics in the Tat(48-57) peptide - Bhosle, Govind S.; Kharche, Shalmali; Kumar, Santosh; Sengupta, Durba; Maiti, Souvik; Fernandes, Moneesha (Chemmedchem, 2018)
We report a 100-fold increase in binding affinity of the Tat(48-57) peptide to HIV-1 transcriptional activator-responsive element (TAR) RNA by replacing Arg52, an essential and critical residue for Tat's specific binding, with (2S,4S)-4-guanidinoproline. The resulting Tat1M peptide is a far superior binder than Tat1M, a peptide containing another conformationally constrained arginine mimic, (2S,4S)-4-amino-N-(3-guanidinopropyl)proline, or even the control Tat peptide (CtrlTat) itself. Our observations are supported by circular dichroism (CD), isothermal titration calorimetry (ITC), gel electrophoresis and UV spectroscopy studies. Molecular dynamics simulations suggest increased interactions between the more compact Tat1M and TAR RNA, relative to CtrlTat. The CD signature of the RNA itself remains largely unchanged upon binding of the peptides. The Tat mimetics further have better cell uptake properties than the control Tat peptide, thus increasing their potential application as specific TAR-binding molecules.
Keywords: antiviral agents; arginine mimics; RNA; Tat peptide analogues; Tat-TAR binding

Conformational plasticity and dynamic interactions of the N-terminal domain of the chemokine receptor CXCR1 - Kharche, Shalmali; Joshi, Manali; Chattopadhyay, Amitabha; Sengupta, Durba (Plos Computational Biology, 2021)
<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">The dynamic interactions between G protein-coupled receptors (GPCRs) and their cognate protein partners are central to several cell signaling pathways. For example, the association of CXC chemokine receptor 1 (CXCR1) with its cognate chemokine, interleukin-8 (IL8 or CXCL8) initiates pathways leading to neutrophil-mediated immune responses. The N-terminal domain of chemokine receptors confers ligand selectivity, but unfortunately the conformational dynamics of this intrinsically disordered region remains unresolved. In this work, we have explored the interaction of CXCR1 with IL8 by microsecond time scale coarse-grain simulations, complemented by atomistic models and NMR chemical shift predictions. We show that the conformational plasticity of the apo-receptor N-terminal domain is restricted upon ligand binding, driving it to an open C-shaped conformation. Importantly, we corroborated the dynamic complex sampled in our simulations against chemical shift perturbations reported by previous NMR studies and show that the trends are similar. Our results indicate that chemical shift perturbation is often not a reporter of residue contacts in such dynamic associations. We believe our results represent a step forward in devising a strategy to understand intrinsically disordered regions in GPCRs and how they acquire functionally important conformational ensembles in dynamic protein-protein interfaces.

Allosteric modulation of the chemokine receptor-chemokine CXCR4-CXCL12 complex by tyrosine sulfation - Sonawani, Archana; Kharche, Shalmali; Dasgupta, Debjani; Sengupta, Durba (International Journal of Biological Macromolecules, 2022)
The chemokine receptor CXCR4 and its cognate ligand CXCL12 mediate pathways that lead to cell migration and chemotaxis. Although the structural details of related receptor-ligand complexes have been resolved, the roles of the N-terminal domain of the receptor and post-translational sulfation that are determinants of ligand selectivity and affinity remain unclear. Here, we analyze the structural dynamics induced by receptor sulfation by combining molecular dynamics, docking and network analysis. The sulfotyrosine residues, 7YsN-term, 12Ys(N-term) and 21Ys(N-term) allow the N-terminal domain of the apo-sulfated receptor to adopt an ``open `` conformation that appears to facilitate ligand binding. The overall topology of the CXCR4-CXCL12 complex is independent of the sulfation state, but an extensive network of protein-protein interactions characterizes the sulfated receptor, in line with its increased ligand affinity. The altered interactions of sulfotyrosine residues, such as 21Ys(N-term)- 47R(CXCL12) replacing the 21Y(N-term)-13F(CXCL12) interaction, propagate via allosteric pathways towards the receptor lumen. In particular, our results suggest that the experimentally-reported receptor-ligand interactions 262D(6.58)- 8R(CXCL12) and 277E(7.28)-12R(CXCL12) could be dependent on the sulfation state of the receptor and need to be carefully analyzed. Our work is an important step in understanding chemokine-receptor interactions and how post-translational modifications could modulate receptor-ligand complexes.
Keywords: Allosteric communication pathway; Atomistic molecular dynamics simulations; G protein-coupled receptor; Ligand binding; Post-translational modification; Protein-protein interface

Graphical Biology Insights into the dynamic interactions at chemokine-receptor interfaces and mechanistic models of chemokine binding - Sonawani, Archana; Kharche, Shalmali; Dasgupta, Debjani; Sengupta, Durba (Journal of Structural Biology, 2022)
Chemokine receptors are the central signaling hubs of several processes such as cell migration, chemotaxis and cell positioning. In this graphical review, we provide an overview of the structural and mechanistic principles governing chemokine recognition that are currently emerging. Structural models of chemokine-receptor cocomplexes with endogenous chemokines, viral chemokines and therapeutics have been resolved that highlight multiple interaction sites, termed as CRS1, CRS1.5 etc. The first site of interaction has been shown to be the Nterminal domain of the receptors (CRS1 site). A large structural flexibility of the N-terminal domain has been reported that was supported by both experimental and simulation studies. Upon chemokine binding, the Nterminal domain appears to show constricted dynamics and opens up to interact with the chemokine via a large interface. The subsequent sites such as CRS1.5 and CRS2 sites have been structurally well resolved although differences arise such as the localization of the N-terminus of the ligand to a major or minor pocket of the orthosteric binding site. Several computational studies have highlighted the dynamic protein-protein interface at the CRS1 site that seemingly appears to resolve the differences in NMR and mutagenesis studies. Interestingly, the differential dynamics at the CRS1 site suggests a mixed model of binding with complex signatures of both conformational selection and induced fit models. Integrative experimental and computational approaches could help unravel the structural basis of promiscuity and specificity in chemokine-receptor binding and open up new avenues of therapeutic design.
Keywords: Chemokine receptors; GPCRs; Intrinsically disordered protein domains; protein-protein interactions

Improved protein dynamics and hydration in the martini3 coarse-grain model - Kharche, Shalmali; Yadav, Manjul; Hande, Vrushali; Prakash, Shikha; Sengupta, Durba (Journal of Chemical Information and Modelling, 2024)
The Martini coarse-grain force-field has emerged as an important framework to probe cellular processes at experimentally relevant time- and length-scales. However, the recently developed version, the Martini3 force-field with the implemented Go model (Martini3Go), as well as previous variants of the Martini model have not been benchmarked and rigorously tested for globular proteins. In this study, we consider three globular proteins, ubiquitin, lysozyme, and cofilin, and compare protein dynamics and hydration with observables from experiments and all-atom simulations. We show that the Martini3Go model is able to accurately model the structural and dynamic features of small globular proteins. Overall, the structural integrity of the proteins is maintained, as validated by contact maps, radii of gyration (Rg), and SAXS profiles. The chemical shifts predicted from the ensemble sampled in the simulations are consistent with the experimental data. Further, a good match is observed in the protein-water interaction energetics, and the hydration levels of the residues are similar to atomistic simulations. However, the protein-water interaction dynamics is not accurately represented and appears to depend on the protein structural complexity, residue specificity, and water dynamics. Our work is a step toward testing and assessing the Martini3Go model and provides insights into future efforts to refine Martini models with improved solvation effects and better correspondence to the underlying all-atom systems.

Benchmarking a dual-scale hybrid simulation framework for small globular proteins combining the CHARMM36 and Martini2 models - Yadav, Manjul; Kharche, Shalmali; Prakash, Shikha; Sengupta, Durba (Journal of Molecular Graphics & Modelling, 2025)
Multi-scale models in which varying resolutions are considered in a single molecular dynamics simulation setup are gaining importance in integrative modeling. However, combining atomistic and coarse-grain resolutions, especially for coarse-grain force fields derived from top-down approaches, have not been well explored. In this study, we have implemented and tested a dual-resolution simulation approach to model globular proteins in atomistic detail (represented by the CHARMM36 model) with the surrounding solvent in Martini2 coarse-grain detail. The hybrid scheme considered is an extension of a model implemented earlier for mainly lipid and water molecules. We have considered a set of small globular proteins and have extensively compared to atomistic benchmark simulations as well as a host of experimental observables. We show that the protein structural dynamics sampled in the hybrid scheme is robust, and the intra-protein contact maps are reproduced, despite increased fluctuations of the loop regions. A good match is observed with experimental small angle X-ray scattering (SAXS) and NMR observables, such as chemical shifts and (3)J((HN-H alpha))-coupling, with the best match obtained for the chemical shifts. However, deviations are observed in the water dynamics and protein-water interactions which we attribute to the limitation of solvent screening in the coarse-grain force field. The computational speed-up achieved is about 2-3 times compared to an all-atom system. Overall, the hybrid model is able to retain the main features of the underlying atomistic conformational landscape with a two-fold speed-up in computational cost.
Keywords: Hybrid simulations; Martini force-field; Mixed models; Multi-scale simulations